2002
DOI: 10.1002/ijc.10298
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of RET, GFRα1 and GDNF genes in Spanish families with multiple endocrine neoplasia type 2A

Abstract: Multiple endocrine neoplasia type 2A (MEN 2A) is associated with specific germline missense mutations in the RET proto-oncogene. This locus encodes a receptor tyrosine kinase whose activation requires the formation of a multimeric receptor complex including GDNF as a ligand and GFR␣1 as a coreceptor. In order to explore the role of RET, GFR␣1 and GDNF genes in the variation of phenotypes observed in MEN2A families, we analysed germline mutations of these genes in 4 unrelated Spanish MEN2A families (23 cases st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 42 publications
(43 reference statements)
2
19
0
Order By: Relevance
“…Even in the presence of GDNF ligand, no valuable transforming activity different from RET-wt background was appreciated. Regarding S904S polymorphism, also detected in the presented patient, strong co-segregation with G691S polymorphism has already been demonstrated (Gil et al 2002, Robledo et al 2003. Both polymorphisms have been shown to be under-represented in Hirschsprung's disease (HSCR, OMIM 142623) patients compared with controls, thus suggesting that they might protect against the development of HSCR (Borrego et al 1999).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Even in the presence of GDNF ligand, no valuable transforming activity different from RET-wt background was appreciated. Regarding S904S polymorphism, also detected in the presented patient, strong co-segregation with G691S polymorphism has already been demonstrated (Gil et al 2002, Robledo et al 2003. Both polymorphisms have been shown to be under-represented in Hirschsprung's disease (HSCR, OMIM 142623) patients compared with controls, thus suggesting that they might protect against the development of HSCR (Borrego et al 1999).…”
Section: Discussionsupporting
confidence: 63%
“…The RET-G691S polymorphism has been suggested as a genetic modifier in MEN2A (Gil et al 2002), but this issue is controversial (Lesueur et al 2006). Conflicting results are also reported with regard to a possible role for this polymorphism in susceptibility to sporadic MTC ( (Fugazzola et al 2008) and references herein).…”
Section: Discussionmentioning
confidence: 93%
“…The polymorphic G691S/S904S variant of RET has been implicated as a modifier factor on the age at which MEN 2A begins (Gil et al 2002, Robledo et al 2003, whereas the RETL769L polymorphism has been previously implicated as having an effect in the early development of hereditary MTC in a family with a mutation in exon 14 (Magalhaes et al 2004). However, we did not observe an association between the presence of these variants and clinical presentation of the disease in hereditary MTC.…”
Section: Discussionmentioning
confidence: 99%
“…15,16,23,43 Robledo et al, 15 for instance, observed that MEN2A patients homozygotes for the SNP A allele were in average 10 years younger than the others and that those younger than 20 years had higher risk of disease, a finding somehow confirmed also in sMTC younger than 45 years. However, the other studies selected for the meta-analysis could not detect any correlation between G691S and age 17,41 or gender, 17 although no details about the analyses performed are reported.…”
Section: Discussionmentioning
confidence: 88%